2010
DOI: 10.1089/aid.2009.0302
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genotypic and Phenotypic Changes in HIV-1-Infected Patients with Virologic Failure on an Etravirine-Containing Regimen in the DUET-1 and DUET-2 Clinical Studies

Abstract: The randomized, placebo-controlled Phase III DUET studies enrolled treatment-experienced, HIV-1-infected patients. We examined the genotypic and phenotypic changes at endpoint relative to baseline, including the emergence of individual reverse transcriptase (RT) mutations, in patients who received the non-nucleoside reverse transcriptase inhibitor (NNRTI) etravirine and experienced virologic failure by rebound by the time of the Week 96 analysis. Patients received etravirine 200 mg twice-daily in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 18 publications
2
53
0
Order By: Relevance
“…Etravirine (ETV; formerly TMC125) and rilpivirine (RPV; formerly TMC278) are potent next-generation NNRTIs that retain activity against efavirenz (EFV)-resistant viruses carrying the K103N mutation in human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) (1, 3); both are diarylpyrimidine (DAPY) compounds. The E138K mutation, which emerges both in vitro and in vivo, confers resistance to ETV and RPV (2,3,22,23). Although in vitro passage experiments suggested that resistance to ETV and RPV emerges more slowly than resistance to first-generation NNRTIs (e.g., nevirapine [NVP] or EFV) (3, 25), this finding has not been confirmed in clinical trials, which show the emergence of ETV and RPV resistance at the time of virologic failure in most patients treated with these drugs (17, 18).…”
Section: Resistance To the Nonnucleoside Reverse Transcriptase Inhibimentioning
confidence: 99%
“…Etravirine (ETV; formerly TMC125) and rilpivirine (RPV; formerly TMC278) are potent next-generation NNRTIs that retain activity against efavirenz (EFV)-resistant viruses carrying the K103N mutation in human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) (1, 3); both are diarylpyrimidine (DAPY) compounds. The E138K mutation, which emerges both in vitro and in vivo, confers resistance to ETV and RPV (2,3,22,23). Although in vitro passage experiments suggested that resistance to ETV and RPV emerges more slowly than resistance to first-generation NNRTIs (e.g., nevirapine [NVP] or EFV) (3, 25), this finding has not been confirmed in clinical trials, which show the emergence of ETV and RPV resistance at the time of virologic failure in most patients treated with these drugs (17, 18).…”
Section: Resistance To the Nonnucleoside Reverse Transcriptase Inhibimentioning
confidence: 99%
“…The phase III DUET clinical trials on the use of ETR in treatment-experienced HIV-1-infected patients showed that substitutions at position V179 were most common among treatment failures, followed by mutations at position E138, among which the E138G and E138Q mutations, but not the E138K mutation, were frequently observed (46). Recently, phase III clinical trials (ECHO and THRIVE) on the use of the combination of RPV-tenofovir disoproxil fumarate (TDF)-emtricitabine (FTC) in drug-naïve patients showed that the most frequent mutations to emerge among virological failures were the mutations E138K and M184I, which are responsible for resistance to FTC and RPV, respectively (34).…”
mentioning
confidence: 99%
“…In patients failing ETR-containing regimens, Y181C was shown to commonly occur (26,42). HIV-1 containing Y181C alone showed moderate-level resistance to ETR (8,41).…”
mentioning
confidence: 99%
“…The E138K mutation was shown to be the first mutation selected by ETR in cell culture passage experiments (5). Viruses containing E138K display moderate resistance to ETR (5,41,47), and E138K has been reported to emerge in HIV-1-infected patients who have failed an ETR-containing regimen (41,42). Thus, E138K has the potential to be an important ETR resistance mutation, particu-larly in the case of wild-type (WT) viruses (6).…”
mentioning
confidence: 99%